Implementasi Keamanan Cyber Berbasis Nilai Nilai Kebangsaan UUD 1945 di Era Digital Best Practice di Perusahaan Pertamina - Thomas Komansilan; Edy Soesanto; Natasha Salsabillah (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
The advancement of digital technology has brought about significant progress across various sectors, while simultaneously introducing new risks, particularly in the realm of cybersecurity. Cybersecurity has become a critical concern for companies, including energy giants like Pertamina. In the context of Indonesia, adherence to cybersecurity within Pertamina must align with relevant legal frameworks, such as the 1945 Constitution (UUD 1945). This research aims to explore optimal approaches to implementing cybersecurity within Pertamina, with a focus on the legal underpinnings of the 1945 Constitution. Key attention is directed towards Article 27, paragraph (3) of the Constitution, which guarantees universal access to education, including information security training for employees—a crucial element in thwarting cyber threats. Furthermore, Article 28, paragraph (1) of the 1945 Constitution, safeguarding freedom of association, can be interpreted to endorse collaboration between Pertamina and external entities, like cybersecurity institutions and regulatory bodies, to bolster cyber defense capabilities. Integration of cutting-edge security technology is paramount, aligning with the principles outlined in Article 33, paragraph (2) of the 1945 Constitution, emphasizing the preservation of natural resources. This extends to safeguarding Pertamina's data and digital infrastructure through measures like encryption technology, robust network security protocols, and effective intrusion detection systems. By heeding the legal foundations provided by the 1945 Constitution, the implementation of cybersecurity at Pertamina must be comprehensive, encompassing employee education, technological upgrades, and collaborative efforts with external stakeholders. Such measures aim to mitigate cyber risks, safeguard operational interests, and shield sensitive information from evolving threats in today's digital landscape. Additionally, Law Number 11 of 2008 plays a crucial role in governing information technology and electronic transactions in Indonesia. This legislation grants legal validity to electronic documents, signatures, and transactions, while also ensuring information security and user privacy. It imposes criminal penalties for illicit activities in the realm of information technology, fostering a secure environment for electronic transactions and upholding user rights in the digital age.